Effect of pruning on the growth and yield of cucumber (Cucumis sativus L.) Mercy Varieties - Gulmat Siregar; Parmanoan Harahap; Wahyuni, Siti Hardianti (Jurnal Agricultural Science, 2024)
This study aims to determine the effect of pruning on the growth and yield of cucumber variety Mercy. This research was organized using a Randomized Group Design (RAK) with treatments, namely: No pruning (P0), pruning shoots on the main stem (P1), pruning shoots of all lateral branches after the third internode (P2) and pruning 2 lateral branches that appear first after the 3rd internode (P3) with 5 replications. The variables observed in this study consisted of; plant length, number of leaves, total number of fruits, number of harvestable fruits, harvestable fruit length, harvestable fruit diameter, and harvestable fruit weight. Data were analyzed using the F test and if there were significant differences followed by the 5% BNT test. The results showed that the treatment without pruning (P0) was able to produce a better number of fruits than the pruning treatment, but the number of fruits produced was of poor quality. The best plant results were found in the shoot pruning treatment on the main stem (P1) because it was able to increase the number of leaves 24.19% compared to no pruning treatment (P0).